Surgical treatment of fracture of the right mandibular angle and left parasymphysis: Clinical case report - Batista, Isabelle Maria Andrade dos Santos; Oliveira, Mateus Ferreira de; Brito, Maria Clara Clark; Lopes, André Coelho (Seven Editora, 2024)
Facial fractures are common in oral and maxillofacial clinical practice, and can be presented in the most diverse ways, despite the different ways in which they are addressed, the functional and aesthetic improvement of the patient is always aimed at the functional and aesthetic improvement, however, when not approached in the correct time and way, they can cause functional and aesthetic problems to the patient. The present study is a clinical case report of fracture of the right mandibular body and left parasymphysis in a 23-year-old male patient, victim of a cycling accident, treated at the General Hospital of the State Professor Osvaldo Brandão Vilela. The treatment of choice was reduction with an Erich bar and maxillomandibular block, followed by fixation of the fragments. . As a result, the treatment of choice was successful, with preservation of the facial contour, reestablishment of a functional and aesthetic occlusion. DOI:https://doi.org/10.56238/sevened2024.001-033